Pengaruh green intellectual capital terhadap Kapitalisasi pasar - Trisari, Otty Trisari; Maria Goreti Kentris Indarti (Universitas Sains dan Teknologi Komputer, 2024)
The purpose and the research conducted is to the investigate and impact of GIC on the market capitalization of each company mentioned in the Indonesian of Stock Exchanges from 2018 to 2022. GIC includes GHC, GSC, and GRC as independent variables. The research data’s derive to from companies of the annual reports mentioned in the Indonesian Stock Exchanges for the specified period. A targeted on sampling methods was the used, which led to at sample of 25 companies. The results of the simple regression linear tests indicate that GIC has a very significant influence on market capitalization. According to Hypothesis 1 (H1), GHC has a very positive and highly significant influence on market capitalization. Similarly, Hypothesis 2 (H2) suggests that GSC can have a significant positive and the impact to the market capitalization, and Hypothesis 3 (H3) states that GRC has a to positive very impact on market capitalization. In addition, the simple regression linear results also show and that the variables of profitability (ROA) and leverage (DAR) have no impact on market capitalization.